TRAINING NEEDS FOR TAIWAN’S INTELLIGENT MEDICAL ELECTRONICS INDUSTRY - Yeh, Ying-Jung Yvonne; chang, yun hsiang (International Journal of Industrial Engineering: Theory, Applications and Practice, 2018)
The Taiwanese government is engaging in positive efforts to develop the emerging intelligent medical electronics industry. Talent is a key element to the development of the industry. The talent needs of Taiwan’s intelligent medical electronics industry require the government’s systematic support and care. Thus, the present study uses the modified Delphi method and workshops to analyze the training needs of the talent for the intelligent medical electronics industry. This study provides 43 knowledge and skill items related to developing the intelligent medical electronics industry during the next five years, which may be used as references for training units when planning their curricula. Additionally, the research results support the recommendation that the government establish a cross-disciplinary exchange mechanism to encourage the electronics industry and medical institutions to interact to facilitate the development of products that meet the demand of such institutions in the future.